ESTUDIO DE RADIO ENLACE DEL SECTOR MATA DE CACAO - EL PLACER DE LA EMPRESA “INTERNET MC” - CHAQUINGA GAVIDIA, KATTY ELIZABETH (2018)
"INTERNET MC" is a company dedicated as an internet provider, established in the Mata de Cacao sector of the Parish Febres Cordero Province of Los Ríos, with the purpose of providing Internet to different sectors, including the Pleasure sector. The present case study will analyze the problems that cause the failures in the communication of data through Radio frequency in the Link Mata de Cacao - El Placer, in which there are problems of low speed in data transmission, intermittency or frequent falling of Radio Enlace causing inconvenience to its customers. This Radio Link consists of connectors, network cables, towers for antennas, radio frequency devices (antennas), POE (Energy over Internet), which allows establishing a communication system between one or several points of a telecommunications infrastructure within a range of distance. In addition, the amount of data to be transported must be kept in mind, as well as the characteristics and standards that must be met for an optimal development of a radio link. A Radio Link allows to transport data and information through radio frequency signals that are sent by the sender and received by the receiver (s). In this network uses devices with frequency of 5ghz. In the security of a radio link, a series of principles (encryption) are established relating to the processing and transmission of data. In addition, many factors of the network formed by a group of devices interconnected with each other must be known. hardware, software and by the telecommunications department with its telecommunications equipment.